OC-029 Dyspepsia management in Malawi: a prospective audit. (28th May 2012) - Keane, M G; Thumbs, A; Hellberg, K; Allain, T; Kankwatira, A; Howson, W; Geraghty, J; Malamba, R; Gordon, M A; O'Toole, P
Abstract : Introduction: Dyspepsia is a very common symptom world wide. Unless managed effectively it can burden endoscopy services and create high treatment costs. Management algorithms are widely used in developed countries but have not been validated in sub-Saharan Africa. In Malawi, Helicobacter pylori (HP) infection rates are high, endoscopy facilities are scarce and proton pump inhibitors (PPIs) expensive. In addition the region has extremely high rates of oesophageal cancer and HIV. The incidence of gastric cancer is not known. These conditions make dyspepsia management particularly challenging. Queen Elizabeth Central Hospital (QECH) in Blantyre is Malawi's tertiary hospital, and provides endoscopy services for a large part of the Southern Region. Methods: A prospective audit of all patients presenting routinely to the outpatient department or endoscopy unit at QECH with dyspeptic symptoms over a 4-week period between August and September 2010. Patients were interviewed and health records and prescriptions reviewed. Results: 105 patients with dyspepsia were identified; 55 already listed for endoscopy. 143 prescriptions for HP eradication were reviewed; 95% of these did not conform to a recognised regimen. Most errors were in dosing or duration but 38% used a H2 receptor antagonist instead of a PPI and 31% included only one antibiotic. The 55 patients undergoing gastroscopy had all received prior HP eradication therapy. Mean symptom duration was 33.8 months. The clinical diagnosis matched endoscopic findings in only 18%. 9% were found to have peptic ulcer disease and "gastritis" was recorded for 35%. There was one gastric cancer and 10 oesophageal cancers. Seven of these 11 patients had dysphagia and malignancy had been suspected; 4/11 malignancies were not suspected. Only 5.5% of endoscopies were normal. Conclusion: Empirical management of dyspepsia in Malawi is poor. HP eradication therapy is given frequently but almost always incorrectly. This is likely to promote antibiotic resistance and make subsequent HP eradication more difficult. Referral criteria for endoscopy are not clear, yet the yield of serious pathology is surprisingly high. The low rate of normal endoscopic findings contrasts with UK practice but may be explained by over-diagnosis of "gastritis". In light of this audit, guidelines on dyspepsia management were developed and implemented. They emphasise correct medical management in young dyspeptic patients without alarm symptoms and urgent referral for gastroscopy if malignancy is suspected at any age. Urease testing has been piloted. The impact of these changes will be assessed later this year. Competing interests: None declared.